2020
DOI: 10.3390/cells9102209
|View full text |Cite
|
Sign up to set email alerts
|

Development of Colonic Organoids Containing Enteric Nerves or Blood Vessels from Human Embryonic Stem Cells

Abstract: The increased interest in organoid research in recent years has contributed to an improved understanding of diseases that are currently untreatable. Various organoids, including kidney, brain, retina, liver, and spinal cord, have been successfully developed and serve as potential sources for regenerative medicine studies. However, the application of organoids has been limited by their lack of tissue components such as nerve and blood vessels that are essential to organ physiology. In this study, we used three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…62 Current models have also utilised the PSC system that can be differentiated towards intestinal organoids, as well as cells of the ENS such as neural crest cells (NCCs). [63][64][65] NCCs that were cocultured with developing intestinal organoids migrated into the mesenchyme, differentiated into neurons and glial cells and showed neuronal activity. 63 ENS-containing intestinal organoids formed neuroglial structures similar to a myenteric and submucosal plexus in vivo.…”
Section: Innervated Organoids (Epithelial-neural Interaction)mentioning
confidence: 99%
See 1 more Smart Citation
“…62 Current models have also utilised the PSC system that can be differentiated towards intestinal organoids, as well as cells of the ENS such as neural crest cells (NCCs). [63][64][65] NCCs that were cocultured with developing intestinal organoids migrated into the mesenchyme, differentiated into neurons and glial cells and showed neuronal activity. 63 ENS-containing intestinal organoids formed neuroglial structures similar to a myenteric and submucosal plexus in vivo.…”
Section: Innervated Organoids (Epithelial-neural Interaction)mentioning
confidence: 99%
“… 73 Indeed, several attempts have been made to introduce iPSC-derived endothelial cells into GI organoids. 65 74 75 Interestingly, a recent study uncovered a population of endothelial cells which are present early in iPSC differentiation towards intestinal organoids that declines over time in culture. This study further developed a method to expand and maintain this endothelial cell popoulation within intestinal organoids as an alternative approach for classical vascularised organoid models.…”
Section: Introductionmentioning
confidence: 99%
“…The development of colonic organoids from PSCs has recently advanced. Park et al [35] reported a method that generated colonic organoids containing enteric nerves or blood vessels by co-culturing nerve cells or endothelial cells with colonic organoids. The NCCs and endothelial cells used in that study were all differentiated from the same hPSC line as the colonic organoids, and integration into organoids was performed after the hindgut was defined from the definitive endoderm.…”
Section: ) Colon (Large Intestine)mentioning
confidence: 99%
“…When combined, vagal NC progenitors generated glia and neurons of the ENS which integrated into the smooth muscle layer of the HIO and were found to promote cell proliferation in intestinal crypts and gene expression indicative of intestinal cell development. More recent work has described the generation of assembloid cultures containing colonic intestinal tissue with ENS and blood vessels; a model perhaps more suited to diseases which impact the distal part of the GI tract, including Crohn's and Hirschsprung's disease [ 88 ].…”
Section: Development In Vitro : Generating Nc Cell...mentioning
confidence: 99%